(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
Corporate Governance has taken center stage in the last few decades in developed as well as developing economies. Corporate Governance is the guiding principle, which determines how companies should be managed to take care of all its stakeholders. Governance of any company is primarily entrusted on its Board of Directors (BODs) or The Board. The main objective of this paper is to study the state of Corporate Governance in India and Singapore, with special emphasis on Corporate Governance aspects related to Boards. A customized questionnaire was deployed to collect primary data for the analysis. The findings reported in the paper are based on analysis conducted on empirical data collected from selected corporate executives from both countries, from diverse industrial segments. Descriptive statistics has been used to present the perception of the participants concerning the proliferation of the corporate governance code parameters related to Board of directors, in the companies across India and Singapore. The study observed that the proliferation of corporate governance codes parameters related to Board of Directors, in the companies across India and Singapore significantly differed in terms of board composition, board development, accountability of the board of directors, remuneration committee, audit committee, risk assessment committee, CSR committee. However, there are still some gaps that need to be bridged.